An Analysis of English Spelling Error Through Dictation Test Made by Seventh Grade Students of Mts Baniy Kholiel - Arinda Eka Utaminingrum; Dihliza Basya; Ribut Sabartono (FKIP Universitas Islam Jember, 2018)
This research aims to investigate English written spelling ability of students, with understanding types of spelling error, and causes of spelling error to prevent students with such repetition of error. Dictation test is used to test students' spelling ability. The subject of this research is seventh grade students of MTs Baniy Kholiel. There were 23 participants and 6 students as sample. The research used descriptive qualitative and error analysis as the research design. The data were collected through dictation test, interview and content analysis. The results found eight types of spelling error, such as; letter add 4%, letter omit 18,05%, transposition letter 0,39%, doubling letter 2,50% , vowel substitution 18,70%, consonant substitution 19,36%, change of word 10%, and missing word 28%. Causes of spelling error are students' weakness on vocabulary mastery, influence of L1, weak in phonological knowledge in stressing letter, blending sound, deletion of sound, and identifying sound in word. Weak in morphological knowledge such as: singular and plural form, and article (a/an and the), and less appropriate instruction of spelling ability in English. Keywords: Spelling error, dictation test, error analysis